Delayed post‐injury administration of C5a improves regeneration and functional recovery after spinal cord injury in mice. (6th October 2013) - Guo, Q.; Cheng, J.; Zhang, J.; Su, B.; Bian, C.; Lin, S.; Zhong, C.
Summary The activation of a complement system can aggravate the secondary injury after spinal cord injury (SCI). However, it was reported recently that the activation of a complement could have both a secondary injury and a neuroprotective effect, in which C5a is the most important factor, but there is no direct evidence for this dual effect of C5a after SCI. In order to investigate the potential neuroprotective effect of C5a after SCI, in this study ectogenic C5a was injected intraperitoneally before/after SCI in vivo, or administrated to mechanically injured neurones in vitro; following this, neurone apoptosis, neurite outgrowth, axonal regeneration and functional recovery were investigated. The in‐vivo experiments indicated that, following treatment with C5a 24 h before or immediately after injury, locomotor function was impaired significantly. However, when treatment with C5a took place 24 h after injury, locomotor function improved significantly. In‐vitro experiments indicated that a certain concentration of C5a (50–100 nM) could inhibit caspase‐3‐mediated neurone apoptosis by binding to its receptor CD88, and that it could even promote the neurite outgrowth of uninjured neurones. In conclusion, delayed post‐injury administration of C5a within a certain concentration could exert its neuroprotective effect through inhibiting caspase‐3‐mediated neurone apoptosis and promoting neurite outgrowth of uninjured neurones as well. These data suggest that C5a may have opposite functions in a time‐ and concentration‐dependent manner after SCI. The dual roles of C5a have to be taken into account when measures are taken to inhibit complement activation in order to promote regeneration after SCI.